Stabilizing Effects of Bacterial Biofilms: EPS Penetration and Redistribution of Bed Stability Down the Sediment Profile. Issue 12 (4th December 2017) - Chen, X. D.; Zhang, C. K.; Zhou, Z.; Gong, Z.; Zhou, J. J.; Tao, J. F.; Paterson, D. M.; Feng, Q.
Abstract: Biofilms, consisting of microorganisms and their secreted extracellular polymeric substances (EPSs), serve as "ecosystem engineers" stabilizing sedimentary environments. Natural sediment bed provides an excellent substratum for biofilm growth. The porous structure and rich nutrients allow the EPS matrix to spread deeper into the bed. A series of laboratory‐controlled experiments were conducted to investigate sediment colonization of Bacillus subtilis and the penetration of EPS into the sediment bed with incubation time. In addition to EPS accumulation on the bed surface, EPS also penetrated downward. However, EPS distribution developed strong vertical heterogeneity with a much higher content in the surface layer than in the bottom layer. Scanning electron microscope images of vertical layers also displayed different micromorphological properties of sediment‐EPS matrix. In addition, colloidal and bound EPSs exhibited distinctive distribution patterns. After the full incubation, the biosedimentary beds were eroded to test the variation of bed stability induced by biological effects. This research provides an important reference for the prediction of sediment transport and hence deepens the understanding of the biologically mediated sediment system and broadens the scope of the burgeoning research field of "biomorphodynamics." Plain Language Summary: In many studies, biofilms have been developed on synthetic material such as glass slides. However, natural sediment beds are very different from impermeable surfaces and provide a more extensive substratum for biofilm growth: the porous structure and rich nutrients allow the biofilm and related extracellular polymeric substance (EPS) matrix to extend deeper into the matrix. A sample of field observation on tidal flats proves this: the biosedimentary layer can be found several centimeters below the surface. Therefore, the biological effects on the sediment bed should not be restricted to simply "surficial protection" such as increasing the erosion threshold. Instead, the EPS expansion into the depth profile alters the properties of a layer of sediment, and thus will certainly have an even greater impact on sediment transport. In the light of this, coastal engineers and morphological prediction modelers are concerned with the following: (1) how do these bioeffects change with depth and time? And (2) what will be the changes to bed stability in response? Therefore, the penetration of bacterial EPS down sediment profile and the depth potential of biostabilization are further investigated in this study. Key Points: The depth profile over biosedimentary beds of different ages is considered Patterns of the bacterial extracellular polymeric substances show natural variation with depth Bed stability within the biosedimentary layer varies due to biological effects